Wyodrębnianie ośrodków odpowiedzialności w przedsiębiorstwach budowlanych według koncepcji zarządzania projektami - Sieradzka-Widz, Anna (Responsibility centres isolation in building enterprises, 2006)
The building enterprises base their activity on building contracts (building projects). This article presents responsibility centers in the building enterprises according to classic approach and according to project management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 365-374